Batik Liquid Waste Management in the Batik Center Area of Tasikmalaya - Meylani, Vita; Mutiara, Frista; Hernawati, Diana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2023)
Batik production in Indonesia is increasing from year to year. However, regarding environmental quality, it is feared that it will produce waste that pollutes the surrounding water bodies. This study aims to describe problems and solutions in improving the management of batik liquid waste in the city and district of Tasikmalaya (Cipedes and Sukaraja) using descriptive qualitative methods and the Miles and Huberman model. The results of the research using interview and observation methods show that most batik SMEs in these two areas have been unable to manage waste optimally. The problem arising from batik liquid waste is the contamination of residents' fish ponds, sewers, and bathtubs. Although there are three independent and communal WWTPs (Wastewater Treatment Plants) in Cipedes (MSME Agnessa, Deden, and riverbanks) as well as one independent WWTP in UMKM Sukapura